Low-Dose Fluvastatin Prevents the Functional Alterations of Endothelium Induced by Short-Term Cholesterol Feeding in Rabbit Carotid Artery - Gulnur Sevin; Yasemin Delen Akcay; Gonen Ozsarlak-Sozer; Mukadder Yasa (The Scientific World Journal)
3-Hydroxy-3-methylglutaryl coenzyme A (HMG-CoA) reductase inhibitors, commonly known as statins, are the medical treatment of choice for hypercholesterolemia. In addition to lowering serum-cholesterol levels, statins appear to promote pleiotropic effects that are independent of changes in serum cholesterol. In this study, we investigated the effects of low-dose fluvastatin on antioxidant enzyme activities (superoxide dismutase, SOD; catalase), total nitrite/nitrate levels, and vascular reactivity in 2% cholesterol-fed rabbits. This diet did not generate any fatty streak lesions on carotid artery wall. However, SOD activity significantly increased with cholesterol feeding whereas the catalase activities decreased. The levels of nitrite/nitrate, stable products of NO degradation, diminished. Moreover, dietary cholesterol reduced vascular responses to acetylcholine, but contractions to serotonin were augmented. Fluvastatin treatment abrogated the cholesterol-induced increase in SOD, increased the levels of nitric oxide metabolites in tissue, and restored both the impaired vascular responses to acetylcholine and the augmented contractile responses to serotonin without affecting plasma-cholesterol levels. Phenylephrine contractions and nitroglycerine vasodilatations did not change in all groups. This study indicated that fluvastatin treatment performed early enough to improve impaired vascular responses may delay cardiovascular complications associated with several cardiovascular diseases.